2007
DOI: 10.1111/j.1478-3231.2006.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of hepatocellular carcinoma in patients with chronic hepatitis C who had a sustained virological response to interferon therapy: a multicenter, retrospective cohort study of 1124 patients

Abstract: SVR patients with CH-C who are elderly, male, or have an advanced histologic stage are at a high risk for the development of HCC after IFN therapy. We recommend that SVR patients should be observed carefully for more than 10 years after the completion of IFN therapy, even if they only have early fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 37 publications
5
62
2
3
Order By: Relevance
“…Similarly, pSmad2L/ C-mediated signaling constitutively induces ECM deposition in pre-neoplastic hepatocytes and HCC by up-regulating PAI-1 transcription [16]. No potentially preventive effects of anti-HCV therapies are able to reduce liver fibrosis and development of HCC once HCV-related cirrhosis is established [10,11]. Consistent with this observation, hepatocytes maintaining high carcinogenic pSmad3L and fibrogenic pSmad2L/C signaling cannot return to tumor-suppressive pSmad3C signaling, even after HCV clearance (Fig.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, pSmad2L/ C-mediated signaling constitutively induces ECM deposition in pre-neoplastic hepatocytes and HCC by up-regulating PAI-1 transcription [16]. No potentially preventive effects of anti-HCV therapies are able to reduce liver fibrosis and development of HCC once HCV-related cirrhosis is established [10,11]. Consistent with this observation, hepatocytes maintaining high carcinogenic pSmad3L and fibrogenic pSmad2L/C signaling cannot return to tumor-suppressive pSmad3C signaling, even after HCV clearance (Fig.…”
Section: Introductionsupporting
confidence: 68%
“…In chronic hepatitis, HCC occurrence clearly depends on continued presence of hepatitis viruses and chronic inflammation. In contrast, patients with cirrhosis have relatively low but real risks of HCC occurrence and hepatic decompensation despite SVR [10,11].…”
Section: Introductionmentioning
confidence: 96%
“…Bolesnici koji su inficirani HCV genotipom 1 i postignu rani virusološki odgovor (HCV rnK pozitivna u 4. nedelji, ali negativna 12. nedelji terapije) leče se 48 nedelja. Odsustvo HCV rnK nakon 48 nedelja lečenja definiše se kao odgovor na kraju terapije (End Tretatmen response -ETr) (28)(29)(30)(31)(32)(33)(34)(35). Trajni virusološki odgovor (Sustained Viral responseSVr) definiše se odsutnošću virusa u krvi (HCV rnK <50 iu/ml), šest meseci nakon završetka terapije.…”
Section: Uvodunclassified
“…All the patients in the study had bridging fibrosis or cirrhosis and the median follow up was 2.1 years. An analysis of 1,124 HCV patients reported that 3.5% of patients with virologic cure developed HCC after a median follow up of 5.8 years (75). The patients with virologic cure who developed HCC were more likely to be male, older, and have more advanced fibrosis compared to patients with a SVR who did not develop HCC.…”
Section: Hcc In Patients Treated With Ifn Based Therapymentioning
confidence: 99%
“…Studies demonstrate that the risk of HCC in individuals who achieve virologic cure is reduced compared to nonresponders (74)(75)(76)(77)(78). In a multicenter retrospective study of 479 HCV patients treated with IFN or PEG-IFN with or without ribavirin, 142 (29.6%) subjects had a sustained response (74).…”
Section: Hcc In Patients Treated With Ifn Based Therapymentioning
confidence: 99%